TEMPERATURE INFLUENCE UPON ELECTROMAGNETIC RADIATION ATTENUATION AND REFLECTION CHARACTERISTICS OF FLEXIBLE WATER-CONTAINING SHIELDS - I. A. Grabar; A. A. Alhamruni; N. V. Nasonova; A. A. Poznyak; G. A. Pukhir (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Temperature dependencies of shielding effectiveness of flexible water-containing shielding materials were studied in the frequency range of 8-12 GHz. It is shown that using the porous materials with a highly developed surface as well as nanostructurizing additives and components for the impregnating solution prevents the decreasing of the shielding effectiveness of the water-containing electromagnetic shields at temperatures below zero.